Astaxanthin-loaded zein/calcium alginate composite microparticles: Characterization, molecular interaction and release kinetics in fatty food simulant system. (December 2020) - Song, Ru; Qi, Yu; Jia, Zhe; Liu, Xinyan; Wei, Rongbian
Abstract: Astaxanthin (Asta), extracted from shrimp ( Litopenaeus vannamei ) by-products, was used to fabricate Asta-loaded zein microparticles coated with resulting calcium alginate (CA) layer. The encapsulation efficiency of Asta to zein/CA (freeze dried, 40 °C or 50 °C oven dried) was across 80%. Some pits were distributed on CA coating layer under scanning electronic microscopy observation. Hydrogen bonding, hydrophobic effects and electrostatic attractions were involved in the interactions of Asta-loaded zein/CA microparticles fabrication by X-ray diffraction, Fourier-transform infrared spectroscopy, and differential scanning calorimetry assays. All of Asta-loaded zein/CA microparticles displayed a two-step biphasic process, initial burst effect followed by subsequent attenuating release, in simulating fatty food system at 4 °C and 25 °C. The cumulative release of Asta from all of the experimental microparticles fit best with Higuchi model at 25 °C. Comparably, the release of Asta from oven dried groups fit best with First-order model (40 °C oven dried group), and Ritger-Peppas model (50 °C oven dried group) at 4 °C. The release kinetics suggested that the release of Asta from the skeleton of the microparticles had a good correlation with time, and could be explained by Fickian diffusion mechanism. Our research proposed a delicate and convenient approach for the controlled release of Asta in fatty food system. Highlights: ●Astaxanthin (Asta) was enwrapped in zein/calcium alginate composite microparticles. ●Encapsulation efficiency of the composite microparticles fabricated was across 85%. ●Asta incorporation caused discontinuous coating layer with pits formation. ●Asta addition induced intermolecular action changes in zein/calcium alginate. ●Fickian diffusion could explain Asta releasing from the composite microparticles.